Prognostička vrednost surfaktantnog proteina D i biohemijskih markera u BALF i plazmi pacijenata sa ARDS-om koji su podvrgnuti mehaničkoj ventilaciji: Prognostic Role of SP-D and Lactate in ARDS - Han, Hu; Zhang, Litao; Guo, Hui; Xu, Xin; Zhao, Xi (Journal of Medical Biochemistry, 2025)
Background: Surfactant protein D (SP-D) and circulating exosomes have emerged as potential biochemical indicators of lung injury severity in acute respiratory distress syndrome (ARDS). This study aimed to evaluate the prognostic value of SP-D levels and selected biochemical parameters in bronchoalveolar lavage fluid (BALF) and plasma among ARDS patients receiving mechanical ventilation.Methods: A total of 103 mechanically ventilated ARDS patients were enrolled between February 2020 and February 2023. Patients were classified into survival (n=59) and death (n=44) groups based on 28-day mortality. On the day of diagnosis, SP-D and exosome levels in BALF and plasma, along with pH, lactate, and oxygenation-related indices, were measured and analyzed for prognostic relevance.Results: SP-D levels in both BALF and plasma were significantly higher in non-survivors (P